Interplay Between Systemic Metabolic Cues and Autonomic Output: Connecting Cardiometabolic Function and Parasympathetic Circuits - Espinoza, Liliana; Fedorchak, Stephanie; Boychuk, Carie R. (Frontiers in Physiology, 2021)
There is consensus that the heart is innervated by both the parasympathetic and sympathetic nervous system. However, the role of the parasympathetic nervous system in controlling cardiac function has received significantly less attention than the sympathetic nervous system. New neuromodulatory strategies have renewed interest in the potential of parasympathetic (or vagal) motor output to treat cardiovascular disease and poor cardiac function. This renewed interest emphasizes a critical need to better understand how vagal motor output is generated and regulated. With clear clinical links between cardiovascular and metabolic diseases, addressing this gap in knowledge is undeniably critical to our understanding of the interaction between metabolic cues and vagal motor output, notwithstanding the classical role of the parasympathetic nervous system in regulating gastrointestinal function and energy homeostasis. For this reason, this review focuses on the central, vagal circuits involved in sensing metabolic state(s) and enacting vagal motor output to influence cardiac function. It will review our current understanding of brainstem vagal circuits and their unique position to integrate metabolic signaling into cardiac activity. This will include an overview of not only how metabolic cues alter vagal brainstem circuits, but also how vagal motor output might influence overall systemic concentrations of metabolic cues known to act on the cardiac tissue. Overall, this review proposes that the vagal brainstem circuits provide an integrative network capable of regulating and responding to metabolic cues to control cardiac function.